Hymenopteran and dipteran larval parasitoid species of the cotton bollworm, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) in chickpea growing districts of Ethiopia. Issue 5 (4th May 2021) - Fite, Tarekegn; Damte, Tebkew; Tefera, Tadele; Negeri, Mulugeta
ABSTRACT: Assessment was conducted to determine the occurrence and estimate parasitism rates of hymenopteran and dipteran parasitoids on Cotton bollworm, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) in chickpea growing districts of Ethiopia. Larval parasitoids of tachinid species Drino sp ., Goniophthalmus halli, Linnaemya cf. longirostris, Pimelimyia sp ., and ichneumonid species, Charops sp., were identified from samples of H. armigera in chickpea. Charops sp. was the most common larval parasitoid species of H. armigera in most of the surveyed districts having varying parasitism rates.